2003
DOI: 10.1136/jech.57.10.823
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of risk factors for symptomatic osteoarthritis of the knee in women using a life course approach

Abstract: Study objective: To explore risk factors for symptomatic knee osteoarthritis (OAK) in women, which included wearing high heeled shoes. Design: Matched case-control study. Exposure information obtained by interview, included details about past footwear. Self reported weight and height data obtained representing when women left school, were aged 36-40 and were aged 51-55. Regular work activities (including periods when homemaker or carer), smoking, and hormone related data gathered using a life-grid. Setting: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
4
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 21 publications
5
68
4
4
Order By: Relevance
“…19,39,41,43 Of these 16 articles, 11 showed a significant positive association between kneeling/knee bending and knee OA with substantial ORs between 1.5 and 6.9. 11,13,14,19,24,25,27,29,30,36,43 Nine papers received a quality score >11, 9,13,14,19,25,29,39,41,43 four of them published after 2004. Six of these articles reported statistically significant results, yet neither of the two cohort studies, 9,22 one of which was high quality, found statistically significant results.…”
Section: Kneeling or Knee Bendingmentioning
confidence: 99%
See 3 more Smart Citations
“…19,39,41,43 Of these 16 articles, 11 showed a significant positive association between kneeling/knee bending and knee OA with substantial ORs between 1.5 and 6.9. 11,13,14,19,24,25,27,29,30,36,43 Nine papers received a quality score >11, 9,13,14,19,25,29,39,41,43 four of them published after 2004. Six of these articles reported statistically significant results, yet neither of the two cohort studies, 9,22 one of which was high quality, found statistically significant results.…”
Section: Kneeling or Knee Bendingmentioning
confidence: 99%
“…These include two cohort studies, 9,22 nine case-control studies that produced 10 articles, 11,13,14,24,25,27,29,30,32,36 and four cross-sectional studies. 19,39,41,43 Of these 16 articles, 11 showed a significant positive association between kneeling/knee bending and knee OA with substantial ORs between 1.5 and 6.9.…”
Section: Kneeling or Knee Bendingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample is thus representative of patients with primary osteoarthritis as it is reported predominantly in women aged 60 years and above [20,21]. Obesity is also a known risk factor as seen in our sample which had an average BMI of 27 [22].…”
Section: Discussionmentioning
confidence: 98%